A new hydryphantid genus from the Tien Shan Mountains of Kazakhstan (Acari, Hydrachnidia: Hydryphantidae) - Smit, Harry (Zootaxa, 2016)
Kazakhithyas pectinatus, n. gen. n. sp., is described from a rheohelocrene spring from the Tien Shan Mountains, Kazakhstan.